The Effect of Accupressure on Hyperemesis Gravidarum and Birth Delivery Pain in Pregnant Women: A Meta Analysis - Fitriana, Alfira; Kristiyanto, Agus; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Nausea and vomiting in pregnancy is a common condition experienced by 50-80% of pregnant women between 6 to 12 weeks of pregnancy. Acupressure stimulation can stimulate and increase blood circulation and vital energy, so as to maintain normal body functions. The purpose of this study was to determine the effect of acupressure on hyperemesis gravidarum and labor pain in pregnant and childbirth women. Subjects and Method: This was a meta-analysis and systematic study. The articles used were obtained from PubMed, Science Direct and Google Scholar. The inclusion criteria used were full text articles with Randomized Control Trial (RCT) design. Research subjects are pregnant women or giving birth. The intervention given was acupressure with the comparison not being given acupressure or fake acupressure, articles published in English and Indonesian. The PICO research problems were as follows: Population= pregnant women and childbirth, Intervention= giving acupressure, Comparison= sham acupressure or without acupressure, Outcome= reduced intensity of nausea and vomiting and labor pain. The study was conducted using an effect size (Standardized Mean Difference). Meta-analysis was carried out using RevMan 5.3 with a random effect model. Results: A total of 20 articles were reviewed in a meta-analysis in this study. Meta-analysis of 9 articles showed acupressure was effective in reducing hyperemesis gravidarum. Pregnant women who received acupressure therapy experienced hyperemesis gravidarum 0.8 units lower than those without acupressure (SMD=-0.84; 95% CI= -1.18 to -0.5; p<0.001). A meta-analysis of 11 articles showed that acupressure was effective in reducing labor pain. Pregnant women who received acupressure therapy experienced labor pain 1.8 units lower than without acupressure (SMD= -1.83; 95% CI= -2.37 to -1.29; p < 0.001). Conclusion: Acupressure can reduce the intensity of nausea and vomiting in pregnant women who experience hyperemesis gravidarum as well as the intensity of labor pain in pregnant women.